Electroreduction of Cr(III) Ions in Methanesulphonate Solution on Pb Electrode - V. S. Protsenko; A. A. Kityk; F. I. Danilov (E-Journal of Chemistry)
The electrochemical reduction of Cr(III) methanesulphonate complexes were investigated on the lead electrode. The Cr(III) electroreduction process proved to be irreversible. The standard rate constants as well as the standard electrode potentials of Cr(III) ions in methanesulphonic acid (MSA) solution are less than those corresponding to the perchlorate electrolytes.